2007
DOI: 10.1111/j.1537-2995.2007.01437.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal genotyping for the K (Kell) and Rh C, c, and E blood groups on cell‐free fetal DNA in maternal plasma

Abstract: Reliable methods have been developed for predicting fetal K, C, c, and E phenotypes, by testing fetal DNA in the plasma samples of pregnant women whose RBCs lack the corresponding antigens. These methods are now being used routinely in a diagnostic service in the United Kingdom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
107
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 37 publications
3
107
0
4
Order By: Relevance
“…Finning et al (2007) were unable to obtain a satisfactory level of specificity by conventional RQPCR methods owing to mispriming of the K (KEL * 1 ) allele-specific primer on the k (KEL * 2 ) allele. This was overcome, with a sacrifice of reduced sensitivity, by employing locked nucleic acids (LNAs) and the introduction of a mismatch into the allele-specific primer.…”
Section: Fetal Genotyping For Other Blood Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finning et al (2007) were unable to obtain a satisfactory level of specificity by conventional RQPCR methods owing to mispriming of the K (KEL * 1 ) allele-specific primer on the k (KEL * 2 ) allele. This was overcome, with a sacrifice of reduced sensitivity, by employing locked nucleic acids (LNAs) and the introduction of a mismatch into the allele-specific primer.…”
Section: Fetal Genotyping For Other Blood Groupsmentioning
confidence: 99%
“…The k/K polymorphism results from a 698C>T SNP in exon 6 of KEL encoding T193M (Lee et al, 1995). There are only a few published reports of noninvasive fetal genotyping for C, c and E (Legler et al, 2002;Hromadnikova et al, 2005;Finning et al, 2007;Orzińska et al, 2008). All involve RQPCR with allele-specific primers or probes.…”
Section: Fetal Genotyping For Other Blood Groupsmentioning
confidence: 99%
“…In previous studies, a good correlation between genotype and phenotype was demonstrated. 12,14 Because delivery occurred in many different hospitals, the determination of the C, c and E phenotype of newborns was not possible in our study population. Therefore, genotyping results for amniotic fluid were used as a reference.…”
Section: Specimens Sample Preparation and Blood Group Serologymentioning
confidence: 99%
“…[8][9][10][11] Whereas numerous studies reporting data for several thousand pregnancies have demonstrated the accuracy of noninvasive prenatal diagnosis of the fetal D type, tests for C, c and E have been investigated in only a few studies with relatively small sample sizes, in which samples were mainly collected later in pregnancy. [12][13][14][15][16] DNA testing earlier in pregnancy has now been established for RhD determination. 17 However, as data are lacking, there is a need to investigate rhesus CcEe (RHCE) alleles in a large study population in early second trimester.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation